THE EFFECT OF PROBLEM BASED LEARNING MODEL ON THE ABILITY TO SOLVE STORY PROBLEMS ON THE AREA OF PLANE SHAPES OF GRADE IV STUDENTS OF SDN LAMBARO ANGAN ACEH BESAR - Aprilianur, Windi; Vitoria, Linda; Safiah, Intan (Universitas Syiah Kuala, 2024)
Problem-solving capacity is classified as one of the objectives of learning mathematics that must be achieved by students to solve problem-based questions. Facts in the field show that there are still students who do not understand the right way to solve word problems. So the purpose of this research is to analyze how problem-based learning influences students' capacity in working on word problems on the area of flat shapes in class IV SDN Lambaro Angan Aceh Besar. The research approach is quantitative with the True-Experimental type and the design is Pretest-Posttest Control Group. The research sample was taken from class IV-A (27 students) as the experimental class and class IV-B (26 students) as the control class. The sampling technique is Random Sampling from the 2 available classes and data is collected using pretest and posttest. The data then used SPSS software version 25 and tested the hypothesis by testing the Independent sample t-test. The value obtained from the statistical data analysis results of the N-Gain Score Test with an average value of 0.70 0.70 is included in the fairly effective category. And the Independent Sample t-test with a significance value (2-tailed) of 0.000 0.05, then the decision-making criteria, namely H1 is accepted and H0 is rejected. So that the conclusion of the research is that the problem based learning model has an effect on the capacity to solve word problems on the material of the flat shape area of class IV SDN Lambaro Angan Aceh Besar.